The Case for Local Ethics Oversight in International Development Research - Cochrane, Logan; Boulanger, Renaud F.; Sheikheldin, Gussai H; Song, Gloria (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2018)
This paper argues that international development research should be submitted to the oversight of research ethics committees from the countries where data will be collected. This includes research conducted by individuals who may fall outside the jurisdictions of most ethics guidelines or policies, such as individuals contracted by non-governmental organizations. The argument is grounded in an understanding of social justice that recognizes that not seeking local ethics approval can be an affront to the decolonization movement, and may lead to significant direct harms to participants. Local ethics oversight can help ensure projects appropriately take into consideration local laws, regulations, priorities and context. For example, a local research ethics committee may be in a better position than a foreign one to assess whether any given proposed project carries context-specific risks. In addition, submitting to a local research ethics committee is to acknowledge the legitimacy of local authorities, thereby taking a stance against the history of colonizing disempowerment. Local oversight is a mechanism to increase the accountability of researchers working abroad: if respect for local authority and tailoring to local context are to be upheld, there must be mechanisms to ensure that research that does not meet these requirements does not proceed. Objections based on the limited oversight capacity in some countries and on concerns related to the politicization of the review process are discussed. Finally, the roles and responsibilities of the various stakeholders in the implementation of greater local ethics oversight are laid out.